2020
DOI: 10.3390/catal10010138
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Removal of Azophloxine via Catalytic Degradation by a Novel Heterogeneous Catalyst under Visible Light

Abstract: Azo dyes are the most widely used synthetic dyes in the printing and dyeing process. However, the discharge of untreated azo dyes poses a potential threat to aqueous ecosystems and human health. Herein, we fabricated a novel heterogeneous catalyst: activated-carbon-fiber-supported ferric alginate (FeAlg-ACF). Together with peroxymonosulfate (PMS) and visible light, this photocatalytic oxidation system was used to remove an azo dye—azophloxine. The results indicated that the proposed catalytic oxidation system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Likewise, an investigation demonstrated that persulfate (PS)based AOPs are also efficient in degrading emerging pollutants from wastewater. 113 The same research indicated that the PS-based Fenton system achieved 96% degradation efficiency for 50 mg L −1 sulfamerazine within a time period of 30 min. 113,114 Meanwhile, when compared with the hybrid system, an investigation by Yang and co-workers revealed that BEF systems have shown the degradation of metoprolol, a betablocker, to be nearly 95% within an HRT of 6 h from the initial pollutant concentration of 10 mg L −1 .…”
Section: Performance Comparison Of Conventional Aops and Integrated Bessmentioning
confidence: 86%
See 1 more Smart Citation
“…Likewise, an investigation demonstrated that persulfate (PS)based AOPs are also efficient in degrading emerging pollutants from wastewater. 113 The same research indicated that the PS-based Fenton system achieved 96% degradation efficiency for 50 mg L −1 sulfamerazine within a time period of 30 min. 113,114 Meanwhile, when compared with the hybrid system, an investigation by Yang and co-workers revealed that BEF systems have shown the degradation of metoprolol, a betablocker, to be nearly 95% within an HRT of 6 h from the initial pollutant concentration of 10 mg L −1 .…”
Section: Performance Comparison Of Conventional Aops and Integrated Bessmentioning
confidence: 86%
“…113 The same research indicated that the PS-based Fenton system achieved 96% degradation efficiency for 50 mg L −1 sulfamerazine within a time period of 30 min. 113,114 Meanwhile, when compared with the hybrid system, an investigation by Yang and co-workers revealed that BEF systems have shown the degradation of metoprolol, a betablocker, to be nearly 95% within an HRT of 6 h from the initial pollutant concentration of 10 mg L −1 . 115 Furthermore, in comparison to the standalone CW system (76.3% removal of SMX with a hydraulic retention time (HRT) of 10 days), the CW-MFC exhibited a signicant improvement in SMX removal, which was mainly due to the integration of both the technologies.…”
Section: Performance Comparison Of Conventional Aops and Integrated Bessmentioning
confidence: 86%
“…The incorporation of intrinsic photosensitive materials such as ferric alginate into adsorbents facilitates the removal of azophloxine because it introduces the relevance of the absorption of light in the overall process. [113] The development of lanthanum oxide ceramic nanowires decorated with nickel nanoparticles exhibited superior performance for the removal of rhodamine B due to the decoration with metal particles and available sites on the fiber surface for the adsorption of contaminants. [114] Similarly, electrospun fibers were prepared by deacetylated cellulose acetate and polydopamine for the adsorption of methylene blue.…”
Section: Dye Removalmentioning
confidence: 99%
“…The incorporation of intrinsic photosensitive materials such as ferric alginate into adsorbents facilitates the removal of azophloxine because it introduces the relevance of the absorption of light in the overall process. [ 113 ]…”
Section: Synthetic Fibersmentioning
confidence: 99%
“…Various heterogeneous catalysts have been widely used for PMS activation to produce highly reactive species. Among these, ironbased catalysts are of particular interest due to their exceptional high performance and cost effectiveness [7,8]. Yet, their application is significantly hindered by the challenges associated with the post-separation of powder-like catalysts from the reaction solution, potential Fe ion leaching and poor mass transport in conventional batch reactors.…”
Section: Introductionmentioning
confidence: 99%